FOR AGRICULTURE IA/IB AND TOURISM GROUP

Business Math 1 -Fina2

Business Math 2 final(1)

Intro ICT

Introduction to Computer (1)

Good morning everyone! 

Good morning everyone!

 

TAGAYTAY INTERNATIONAL CONVENTION CENTER

THE BEST

MANUEL L. QUEZON DAY ANNIVERSARY

http://www.filipinowriter.com/manuel-luis-quezon-isang-paggunita

Result of First Grading Grades of 2nd year and 4th year Mathematics

4th yr #2

Evaluating Functions

1) f(x)=-(7)/(8)+x(2x-7)-x x=4
A. -(9)/(6)
B. -(7)/(5)
C. -(7)/(8)
D. -(5)/(3)

2) f(x)=(x+6)(-x+2)-(x)/(3) x=2
A. -(4)/(6)
B. -(2)/(3)
C. -(8)/(6)
D. -(6)/(5)

3) f(x)=2x-(7(x+3))/(3)+(3x+7)(x-2) x=6
A. 44
B. 91
C. 22
D. 89

4) f(x)=-(8)/(2)-(8(-4+3x))/(3) x=5
A. -(100)/(3)
B. -(496)/(4)
C. -(638)/(4)
D. -(429)/(6)

5) f(x)=-7(x+2)-8+(5(x-4))/(4) x=3
A. -(177)/(4)
B. -(493)/(6)
C. -(545)/(6)
D. -(335)/(7)

6) f(x)=(x-6)-(-2x+5)/(4)+(7(5-2x))/(3) x=3
A. -(79)/(76)
B. -(84)/(96)
C. -(61)/(12)
D. -(73)/(97)

7) f(x)=-(x-8)/(5)+2-6(8+2x) x=0
A. -(875)/(3)
B. -(227)/(3)
C. -(222)/(5)
D. -(897)/(5)

8) f(x)=-7(x-3)-(x)/(8)-(3x(-2x-2))/(2) x=3
A. (893)/(3)
B. (285)/(8)
C. (683)/(5)
D. (292)/(3)

9) f(x)=-(2(-x+4))/(2)-4(x+7) x=7
A. -59
B. -53
C. -64
D. -98

10) f(x)=-(3x)/(5)-6-(5(7-x))/(7) x=8
A. -(897)/(85)
B. -(353)/(35)
C. -(687)/(26)
D. -(699)/(38)

11) f(x)=-2(-2x-8)+(x-2)(x-6)+6 x=5
A. 34
B. 68
C. 39
D. 97

12) f(x)=-4(-3x+6)+(x+2)/(7) x=2
A. (4)/(7)
B. (4)/(8)
C. (8)/(9)
D. (6)/(8)

13) f(x)=((x+4)(x-3))/(2)-(6(-4+3x))/(2)+(2x)/(4) x=1
A. -(5)/(9)
B. -(3)/(2)
C. -(3)/(8)
D. -(7)/(8)

14) f(x)=3+((x+6)(-2x-3))/(4)-8(3+x) x=4
A. -(674)/(8)
B. -(465)/(2)
C. -(161)/(2)
D. -(696)/(2)

15) f(x)=3(x+5)-6(-2+3x)-2 x=6
A. -46
B. -65
C. -69
D. -29

16) f(x)=8(x-6)+6(-8-x)+(x-7)(-3x+3) x=5
A. -62
B. -85
C. -64
D. -86

17) f(x)=(8)/(7)-(2x)/(2) x=6
A. -(93)/(8)
B. -(34)/(7)
C. -(35)/(2)
D. -(94)/(2)

18) f(x)=5(7-3x)+3x(3x+4)-(6(7-3x))/(7) x=2
A. (266)/(5)
B. (856)/(7)
C. (736)/(9)
D. (449)/(7)

19) f(x)=(x+4)/(4)-(2(x-3))/(5)+7(-2-2x) x=0
A. -(62)/(3)
B. -(48)/(3)
C. -(37)/(4)
D. -(59)/(5)

20) f(x)=-5(6-3x)-2x(-3x+6)-4(-6-2x) x=2
A. 89
B. 40
C. 68
D. 83

21) f(x)=6+(2)/(2) x=0
A. 7
B. 2
C. 6
D. 5

22) f(x)=(x-7)(x-6)-(8(x-4))/(2) x=4
A. 7
B. 3
C. 6
D. 2

23) f(x)=(8(-5-3x))/(4)+2x-(3x)/(3) x=3
A. -76
B. -55
C. -33
D. -25

24) f(x)=-3x-6(x+2)+2(7+2x) x=4
A. -18
B. -99
C. -57
D. -97

25) f(x)=-x+x(-2x+7) x=4
A. -3
B. -5
C. -8
D. -2

4th Year Sample Questions

Simplifying Functions

1) f(x)=10-6(8+3x)
A. f(x)=-89x-59
B. f(x)=-18x-38
C. f(x)=-24x-69
D. f(x)=-54x-24

2) f(x)=-3(-x+0)-7(9-x)
A. f(x)=10x-63
B. f(x)=45x-52
C. f(x)=86x-86
D. f(x)=98x-25

3) f(x)=-5(-6+3x)+x
A. f(x)=-14x+30
B. f(x)=-74x+83
C. f(x)=-35x-37
D. f(x)=-47x+57

4) f(x)=-4+2x
A. f(x)=6x-3
B. f(x)=7x-5
C. f(x)=2x-4
D. f(x)=3x-6

5) f(x)=(x+8)-5(-7+3x)+8
A. f(x)=-27x+77
B. f(x)=-32x-87
C. f(x)=-72x-43
D. f(x)=-14x+51

6) f(x)=2(x+9)-3x
A. f(x)=-x+74
B. f(x)=-x+35
C. f(x)=-x-57
D. f(x)=-x+18

7) f(x)=(7(-9-2x))/(10)-9(-3+3x)+(5)/(2x)
A. f(x)=(-989x^(2)+588x+94)/(94x)
B. f(x)=(-585x^(2)+992x+62)/(37x)
C. f(x)=(-284x^(2)+207x+25)/(10x)
D. f(x)=(-637x^(2)-928x-78)/(24x)

8) f(x)=(3(-3+2x))/(2)+2x
A. f(x)=(10x-9)/(2)
B. f(x)=(44x-5)/(3)
C. f(x)=(67x-7)/(3)
D. f(x)=(27x-2)/(6)

9) f(x)=(3)/(2x)+(-2x-7)(x-8)+(x-6)
A. f(x)=(-2x^(3)+34x^(2)+333x+9)/(5x)
B. f(x)=(-4x^(3)+20x^(2)+100x+3)/(2x)
C. f(x)=(-6x^(3)+48x^(2)+645x+5)/(3x)
D. f(x)=(-8x^(3)-62x^(2)-653x-6)/(9x)

10) f(x)=10(x-2)-6
A. f(x)=49x-86
B. f(x)=89x-39
C. f(x)=94x-59
D. f(x)=10x-26

11) f(x)=-4(x+2)-8(-6+3x)+3x(-x+3)
A. f(x)=-4x^(2)-84x-83
B. f(x)=-6x^(2)-26x+85
C. f(x)=-3x^(2)-19x+40
D. f(x)=-2x^(2)-39x+35

12) f(x)=-3(-7+x)-3x+0(-3x+8)
A. f(x)=-6x-34
B. f(x)=-2x-38
C. f(x)=-4x+62
D. f(x)=-6x+21

13) f(x)=(4)/(2x)+4(x-10)
A. f(x)=(3(8x^(2)-32x+7))/(x)
B. f(x)=(2(2x^(2)-20x+1))/(x)
C. f(x)=(5(3x^(2)-52x-9))/(x)
D. f(x)=(9(3x^(2)-95x-9))/(x)

14) f(x)=-3(-2-x)-4(-8-2x)+10(x-6)
A. f(x)=44x-54
B. f(x)=67x-74
C. f(x)=21x-22
D. f(x)=27x-27

15) f(x)=(7)/(x)+(x+4)(x+8)
A. f(x)=(x^(3)-38x^(2)-72x-2)/(x)
B. f(x)=(x^(3)-78x^(2)-26x-2)/(x)
C. f(x)=(x^(3)+93x^(2)+46x+4)/(x)
D. f(x)=(x^(3)+12x^(2)+32x+7)/(x)

16) f(x)=-2(-2x-7)+(4)/(2x)
A. f(x)=(7(5x^(2)-6x-5))/(x)
B. f(x)=(2(2x^(2)+7x+1))/(x)
C. f(x)=(2(5x^(2)-2x-9))/(x)
D. f(x)=(4(8x^(2)+4x+9))/(x)

17) f(x)=(9(x+7))/(3)+5(-x-8)+(4)/(x)
A. f(x)=(-2x^(2)-19x+4)/(x)
B. f(x)=(-8x^(2)-28x+2)/(x)
C. f(x)=(-4x^(2)-23x+5)/(x)
D. f(x)=(-5x^(2)-55x-5)/(x)

18) f(x)=(5)/(6)+6-6(x+5)
A. f(x)=-2x-(796)/(4)
B. f(x)=-6x-(139)/(6)
C. f(x)=-3x-(236)/(5)
D. f(x)=-7x-(279)/(6)

19) f(x)=(x+5)(x+10)+(2x+10)(x-3)
A. f(x)=5x^(2)-85x-49
B. f(x)=7x^(2)+37x+42
C. f(x)=3x^(2)-33x-82
D. f(x)=3x^(2)+19x+20

20) f(x)=(x+4)(x+5)-7(-2x+6)-5(x-9)
A. f(x)=x^(2)+67x+39
B. f(x)=x^(2)+18x+23
C. f(x)=x^(2)+27x+65
D. f(x)=x^(2)+32x+85

21) f(x)=-7-6(-10-2x)
A. f(x)=12x+53
B. f(x)=98x+74
C. f(x)=23x-93
D. f(x)=63x-57

22) f(x)=-(3(10+3x))/(5)+3x+(x-5)
A. f(x)=(11(x-5))/(5)
B. f(x)=(63(x-6))/(5)
C. f(x)=(76(x-8))/(5)
D. f(x)=(36(x-3))/(8)

23) f(x)=-(2(x+2))/(2)-5(3-2x)+9(10-3x)
A. f(x)=-86x+53
B. f(x)=-29x-73
C. f(x)=-18x+73
D. f(x)=-69x-27

24) f(x)=(7(x-5))/(5)-3x-7(7+2x)
A. f(x)=-(9(26x+635))/(4)
B. f(x)=-(6(86x+256))/(6)
C. f(x)=-(2(39x+140))/(5)
D. f(x)=-(7(38x-265))/(6)

25) f(x)=-(7)/(x)-2(x-6)
A. f(x)=(-2x^(2)+76x-6)/(x)
B. f(x)=(-9x^(2)-33x-8)/(x)
C. f(x)=(-9x^(2)-88x-2)/(x)
D. f(x)=(-2x^(2)+12x-7)/(x)